Multi-institutional phase ii clinical study of concurrent chemoradiotherapy for locally advanced cervical cancer in east and southeast asia - Kato, S.; Ohno, T.; Thephamongkhol, K.; Chansilpa, Y.; Yuxing, Y.; Devi, C.R.B.; Bustam, A.Z.; Calaguas, M.J.C.; de los Reyes, R.H.; Cho, Chul-Koo; Dung, T.A.; Supriana, N.; et al. (Elsevier, 2010)
Purpose: To evaluate the toxicity and efficacy of concurrent chemoradiotherapy using weekly cisplatin for patients with locally advanced cervical cancer in East and Southeast Asia, a multi-institutional Phase II clinical study was conducted among eight Asian countries. Methods and Materials: Between April 2003 and March 2006, 120 patients (60 with bulky Stage IIB and 60 with Stage IIIB) with previously untreated squamous cell carcinoma of the cervix were enrolled in the present study. Radiotherapy consisted of pelvic external beam radiotherapy (total (lose, 50 Gy) and either high-dose-rate or low-dose-rate intracavitary brachytherapy according to institutional practice. The planned Point A dose was 24-28 Gy in four fractions for high-dose-rate-intracavitary brachytherapy and 40-45 Gy in one to two fractions for low-dose-rate-intracavitary brachytherapy. Five cycles of weekly cisplatin (40 mg/m(2)) were administered during the radiotherapy course. Results: All patients were eligible for the study. The median follow-up was 27.3 months. Of the 120 patients, 100 (83%) received four or five cycles of chemotherapy. Acute Grade 3 leukopenia was observed in 21% of the patients, and Grade 3 gastrointestinal toxicity was observed in 6%. No patient failed to complete the radiotherapy course because of toxicity. The 2-year local control and overall survival rate for all patients was 87.1% and 79.6%, respectively. The 2-year major late rectal and bladder complication rate was 2.5% and 0%, respectively. Conclusion: The results have suggested that concurrent chemoradiotherapy using weekly cisplatin is feasible and effective for patients with locally advanced cervical cancer in East and Southeast Asia. (C) 2019 Elsevier Inc.